-4n(2n+3)=8

Simple and best practice solution for -4n(2n+3)=8 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -4n(2n+3)=8 equation:


Simplifying
-4n(2n + 3) = 8

Reorder the terms:
-4n(3 + 2n) = 8
(3 * -4n + 2n * -4n) = 8
(-12n + -8n2) = 8

Solving
-12n + -8n2 = 8

Solving for variable 'n'.

Reorder the terms:
-8 + -12n + -8n2 = 8 + -8

Combine like terms: 8 + -8 = 0
-8 + -12n + -8n2 = 0

Factor out the Greatest Common Factor (GCF), '-4'.
-4(2 + 3n + 2n2) = 0

Ignore the factor -4.

Subproblem 1

Set the factor '(2 + 3n + 2n2)' equal to zero and attempt to solve: Simplifying 2 + 3n + 2n2 = 0 Solving 2 + 3n + 2n2 = 0 Begin completing the square. Divide all terms by 2 the coefficient of the squared term: Divide each side by '2'. 1 + 1.5n + n2 = 0 Move the constant term to the right: Add '-1' to each side of the equation. 1 + 1.5n + -1 + n2 = 0 + -1 Reorder the terms: 1 + -1 + 1.5n + n2 = 0 + -1 Combine like terms: 1 + -1 = 0 0 + 1.5n + n2 = 0 + -1 1.5n + n2 = 0 + -1 Combine like terms: 0 + -1 = -1 1.5n + n2 = -1 The n term is 1.5n. Take half its coefficient (0.75). Square it (0.5625) and add it to both sides. Add '0.5625' to each side of the equation. 1.5n + 0.5625 + n2 = -1 + 0.5625 Reorder the terms: 0.5625 + 1.5n + n2 = -1 + 0.5625 Combine like terms: -1 + 0.5625 = -0.4375 0.5625 + 1.5n + n2 = -0.4375 Factor a perfect square on the left side: (n + 0.75)(n + 0.75) = -0.4375 Can't calculate square root of the right side. The solution to this equation could not be determined. This subproblem is being ignored because a solution could not be determined. The solution to this equation could not be determined.

See similar equations:

| 5x^2-4x+1=673 | | -5t^2+24t+36=0 | | -7v-40=9(v-8) | | (39200+-8x)=-770 | | 2(w+9)=7w-2 | | 8(4900-x)=770 | | 8v-7=-3(v+6) | | -6x+5.4=6.3+1.2x | | x/3=15/2 | | (1/(ab))/(1/(ab^2))/(1/(a^2b)) | | 2x(x+3)=-15 | | 216=45t | | x^4(a-b)+16(b-a)=0 | | 0.30x+0.05(20-x)=0.10(-10) | | Log(x^2-9)-3=log(x+3) | | 1/2w-2/3=2/3 | | H*t=128t-16t^2 | | 3x/9x= | | 9-5/2= | | (5x-6)(2x+9)= | | 0=-0.125x^2+0.35x+0.75 | | 4(x-2)4x+10= | | Log(x^2-9)-log(x+3)=3 | | y=-0.125x^2+0.35x+0.75 | | -2v+34=8(v+3) | | (4x^2-3x^3)-(8x^2-5x^3)= | | 17z-6z+3= | | 5w^2-3w=17 | | 9x^2/lnx | | 8(u+4)=-2u+12 | | 100=-0.1x+1 | | x^2-12x+36=352 |

Equations solver categories